The Impact of Digital Technology on Exports in Services in EU Countries: A Panel Data Approach - Mariola PIŁATOWSKA (Communications of International Proceedings, 2025)
This paper aims to demonstrate the impact of digital technology on service exports in EU countries and within subgroups of countries divided by GDP per capita (lower and higher-income countries). We use the Digital Economy and Society Index (DESI) and its components as proxies for the level of digitalization in a country and the value of digitally delivered services as a proxy for service exports. To examine relevant relationships, we employ a panel data model on EU countries from 2017 to 2022. Results show that in all EU countries and within their subgroups, DESI has a positive and significant effect on service exports. However, the importance of the main components of DESI varies. Additionally, the influence of digital transformation is more pronounced in lower-income countries. The findings indicate that the digital skills of human capital are key factors that enhance service exports. Therefore, these skills are essential for the absorption and dissemination of digital technology, which in turn boosts service exports and promotes economic growth and social modernization.
Keywords: Digital technology; DESI; service exports; lower and higher-income countries.